2010
DOI: 10.1186/1472-6874-10-6
|View full text |Cite
|
Sign up to set email alerts
|

New paradigm old thinking: the case for emergency obstetric care in the prevention of maternal mortality in Nigeria

Abstract: BackgroundThe continuing burden of maternal mortality, especially in developing countries has prompted a shift in paradigm from the traditional risk assessment approach to the provision of access to emergency obstetric care services for all women who are pregnant. This study assessed the knowledge of maternity unit operatives at the primary and secondary levels of care about the concept of emergency obstetric care (EmOC) and investigated the contents of antenatal care (ANC) counseling services they delivered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 4 publications
2
39
1
1
Order By: Relevance
“…This finding on good knowledge of BPACR among HCPs identified in this study is in contrast to findings reported from a study [9] in IleIfe South Western Nigeria which revealed a poor knowledge among health care providers on the concept of Emergency Obstetric Care. This finding is worrisome as majority of these health care providers reported in the study [9] to have conducted counselling and health education sessions for pregnant women on BPACR during ANC sessions and as such could have communicated wrong information to unsuspecting clients and these can negatively influence their knowledge base and their decision making ability in taking up appropriate health intervention and making informed decision under emergency situation.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…This finding on good knowledge of BPACR among HCPs identified in this study is in contrast to findings reported from a study [9] in IleIfe South Western Nigeria which revealed a poor knowledge among health care providers on the concept of Emergency Obstetric Care. This finding is worrisome as majority of these health care providers reported in the study [9] to have conducted counselling and health education sessions for pregnant women on BPACR during ANC sessions and as such could have communicated wrong information to unsuspecting clients and these can negatively influence their knowledge base and their decision making ability in taking up appropriate health intervention and making informed decision under emergency situation.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is worrisome as majority of these health care providers reported in the study [9] to have conducted counselling and health education sessions for pregnant women on BPACR during ANC sessions and as such could have communicated wrong information to unsuspecting clients and these can negatively influence their knowledge base and their decision making ability in taking up appropriate health intervention and making informed decision under emergency situation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…9 Nigerian studies identified reduced knowledge of active management of third stage of labor among maternity health care providors. 10,11 Despite safe motherhood and neonatal health programme is a focused health programmes of Nepal, this initiative yet to be evaluated. 12 So, this research was conducted to assess the critical knowledge of maternal and newborn care among nursing personnel working under primary level health care facilities in Kapilvastu District of Nepal.…”
Section: Introductionmentioning
confidence: 99%